MENINGKATKAN PRESTASI BELAJAR DENGAN METODE JIGSAW DALAM PEMBELAJARAN IPS POKOK BAHASAN PELESTARIAN MAKHLUK HIDUP PADA KELAS V SEMESTER I SD NEGERI BLOTONGAN 01 SALATIGA - Regita Kusuma Dewi (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2019)
The purpose of this study was to describe the application of the 2013 Curriculum Based Jigsaw learning technique and improve student learning achievement. The subjects used were the fifth grade students of Blotongan District Elementary School 01 Salatiga 1st Semester 2019/2020 Year with a total of 25 students. The technique used in this study is class action research or PTK which consists of two cycles. Each cycle consists of the stages of planning, action, observation and reflection. Data retrieval used is a test in the form of test questions and non-tests in the form of observation or direct observation. Data analysis was performed by quantitative techniques. In the first cycle the final score achieved was an average of 71.28. In the second cycle the number of final grades managed to rise with an average value of 79.32. Thus there was an increase of 8.04. Based on the analysis of the results of the study, the Jigsaw method succeeded in increasing the learning achievement of students in the first cycle of 72.35% and the second cycle of 82.50%. The application of the jigsaw learning method is proven to increase the enthusiasm and results of student learning achievemen